Causality of lap times with total time in slalom - Bilic, Z.; Mijanovic, M. (Acta Kinesiologica, 2008)
The issues which can be best described as the existing rules for skiers` behavior in a race for the World cup in two runs were studied in this article. After the precise data from the run in the race for the world cup in Zagreb had been collected and using the factor and regression models, it was shown that there existed some relationship which was recognized as the importance of the second run in regard to the total result, which also has a bigger predictive value on the total achievement. The reasons for this can be found in calculations related to the final result and in the tactical way of ride. In the practical sense, the results rationalize two runs, especially when the best 30 skiers from the first run participate in the second ride. It is supposed then that the conclusions transparency on to other rides is very high but it is suggested to examine that hypothesis, too.